2022
DOI: 10.1039/d1fo03929f
|View full text |Cite
|
Sign up to set email alerts
|

Structure of type II collagen from sturgeon cartilage and its effect on adjuvant-induced rheumatoid arthritis in rats

Abstract: The purpose of this paper was to extract and characterize type II collagen of sturgeon cartilage (SC-CII), and to explore the effects of taking SC-CII orally on rheumatoid arthritis (RA)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…In this sense, several active substances such as polysaccharide, protein (especially collagen), and peptides were previously obtained from the cartilage of marine organisms, such as sharks, sturgeon, rays and stingrays. For instance, many recent studies reported the potential availability of cartilages for extraction of chondroitin sulfate from shark [ 1 , 2 ], antioxidant collagen peptides from Siberian sturgeon ( Acipenser baerii ) [ 3 ], type II collagen from skate and sturgeon [ 4 , 5 ], gelatin from Siberian sturgeon ( Acipenser baerii ) [ 6 ], collagenous polypeptide (37 kDa) prepared from whale shark cartilage ( Rhincodon typus ) [ 7 ] and low-molecular-weight protein from shark [ 8 ]. Among these biomolecules, collagen is the most abundant fibrous structural protein in animals, accounting for approximately 30% of the total protein of the human body [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, several active substances such as polysaccharide, protein (especially collagen), and peptides were previously obtained from the cartilage of marine organisms, such as sharks, sturgeon, rays and stingrays. For instance, many recent studies reported the potential availability of cartilages for extraction of chondroitin sulfate from shark [ 1 , 2 ], antioxidant collagen peptides from Siberian sturgeon ( Acipenser baerii ) [ 3 ], type II collagen from skate and sturgeon [ 4 , 5 ], gelatin from Siberian sturgeon ( Acipenser baerii ) [ 6 ], collagenous polypeptide (37 kDa) prepared from whale shark cartilage ( Rhincodon typus ) [ 7 ] and low-molecular-weight protein from shark [ 8 ]. Among these biomolecules, collagen is the most abundant fibrous structural protein in animals, accounting for approximately 30% of the total protein of the human body [ 9 ].…”
Section: Introductionmentioning
confidence: 99%